Isolation and Identification of Andrographolide Compounds from the Leaves of Sambiloto Plant (Andrographis paniculata Ness) - Devi Ayu Septiani; Aliefman Hakim; Lalu Raftha Patech; Zulhalifah Zulhalifah; Siswadi Siswadi (The University of Mataram, 2021)
Sambiloto plant (Andrographis paniculata Ness) is a plant that has been used as medicine from generation to generation. Bioactive compounds in Sambiloto have pharmacological effects such as immunostimulants (increase immunity), antibiotic diuretics (facilitate urine), antipyretics, anti-inflammatory (anti-inflammatory), hepatoprotective, hypotensive, hypoglycemic, antibacterial, anti-inflammatory, respiratory tract, and heart and lung meridians - lungs. The bioactive compound in Sambiloto which is mostly found in the leaves is Andrographolide. In this study, the isolation of Andrographolide from the leaves of the sambiloto plant (Andrographis paniculata Ness) was carried out using purification and crystallization methods aimed at obtaining pure Andrographolide isolates more efficiently and identifying the results of Andrographolide isolates. The results showed that the isolates obtained using the purification and crystallization methods obtained a yield of 0.47%. In the qualitative test of Andrographolide isolates using eluent and acetate: n-hexane (3: 2), the Rf value was 0.38. The results obtained from Andrographolide isolates using infrared spectroscopy (FT-IR) were identical to the literature on Andrographolide. The absorption peaks at the wavenumbers obtained includes 3400,41 cm-1, 1979,68 cm-1, 1959,46 cm-1, 2928,22 cm-1, 1727,56 cm-1, 1646,98 cm-1, and 907,53 cm-1.